GROWTH PERFORMANCE AND ECONOMIC BENEFITS OF FEEDING CRUSHED WHOLE COTTONSEED AND BAKERâ€™S YEAST (SACCHROMYCES CEREVISIAE) INCLUSION IN THE RATIONS OF RED SOKOTO BUCKS - Yakubu, Laraba; ABdu, Salisu Bakura; Lamidi, Owolabi S.; Adamu, Hanwa Yusuf; Yashim, Suleiman Makama; Musa, A.; Millam, Jacob Jafiya (FUDMA JOURNAL OF SCIENCES, 2022)
The study was conducted to evaluate growth rate and profitability of Red Sokoto bucks fed Sacchromyces cerevisiae inclusion in diets containing varied levels of Crushed Whole Cotton Seed (CWCS). A total of 20 bucks weighing an average of 12 kgÂ±0.25 kg were randomly assigned to five experimental diets formulated to contain 14% crude protein in complete diets at varied levels of 10% CWCS without yeast inclusion and 10, 15, 20 and 25% CWCS with500 g yeast (Y) inclusion across these four (4) treatment groups. Bucks were fed at 3.5% of their body weights throughout the trial period that lasted for 90 days in a completely randomized design. Feed intake was highest at 15% CWCS +Yeast (26.11 kg) inclusion level likewise; Total weight gain (3.25 kg) and Average daily gain (290.13 g). Cost/kg of feed and cost of feeding increased as CWCS inclusion increased. Cost/kg gain (839.94 naira) and value of gain (2275.00 naira) were best at 15% CWCS. Yeast supplementation at 15% crushed whole cotton seed inclusion gave higher values of weight gain, cost per kilogram gain and value of gain of bucks thus yeast supplementation can be encouraged amongst goat farmers feeding whole cottonseed in diets.